2022
DOI: 10.3389/fonc.2022.933964
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic study of mantle cell lymphoma with epstein-barr virus infection: A case series and literature review

Abstract: BackgroundMantle cell lymphoma (MCL) with Epstein–Barr virus (EBV) infection is rarely reported. The objective of this study was to analyze the prevalence and clinicopathological features of MCL with EBV infection in the largest series thus far.MethodsAfter screening 138 cases of MCL, we identified eight cases of MCL with EBV infection.ResultsMost of them (7/8) had non-neoplastic bystander cells with positivity for EBV and no expression of latent membrane protein 1 (LMP1) and EBV nuclear antigen 2 (EBNA2). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Although MCL is not usually considered an EBV + lymphoma [ 16 ], EBV can infect MCL in rare cases. Among patients with MCL, the incidence of EBV + MCL is low, with one report reporting an infection rate of 5.8% [ 6 ]. Interestingly, this study found that clinical and pathological findings were comparable between EBV+ and EBV-negative MCL patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MCL is not usually considered an EBV + lymphoma [ 16 ], EBV can infect MCL in rare cases. Among patients with MCL, the incidence of EBV + MCL is low, with one report reporting an infection rate of 5.8% [ 6 ]. Interestingly, this study found that clinical and pathological findings were comparable between EBV+ and EBV-negative MCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…The association between EBV and MCL has rarely been reported, with an estimated incidence of approximately 5.8% of reported MCL cases being EBV-positive. EBV + cells in MCL varied in number, and interestingly, most of the EBV + cells are background CD3+ T cells, instead of tumor cells [ 6 ]. Furthermore, the EBV-associated transformation of MCL has rarely been reported [ 7 ], and the role of EBV in MCL transformation remains unclear.…”
Section: Introductionmentioning
confidence: 99%